Analysis of Patient Satisfaction with Third-Class Inpatients at Pertamina Bintang Amin Husada Hospital, Bandar Lampung - Shabrina Elta Kusmana, Airin; -, Adinda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
The 1945 Constitution of the Republic of Indonesia affirms that everyone has the right to receive health services. Hospitals are one of the health services, and as a health service, a hospital's ability to meet patient needs can be measured by the level of patient satisfaction, which is based on five principles of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Therefore, patients who are satisfied with hospital services will have a positive impact and benefit the hospital, while dissatisfied patients will be detrimental to the hospital. The purpose of this study was to analyze the satisfaction of third-class inpatients at Pertamina Bintang Amin Husada Hospital, Bandar Lampung. This study was quantitative with a cross-sectional design. Accidental sampling was used, selecting 105 respondents who met the inclusion criteria. Data analysis used chi-square analysis and multivariate analysis using logistic regression. The results showed that most of the patients were satisfied, amounting to 63 patients (60%), and the dimensions of the quality of health services in the Hospital were tangible, mostly good, amounting to 66 patients (62.9%), reliability, mostly good, amounting to 61 patients (58.1%), responsiveness, mostly good, amounting to 69 patients (65.7%), assurance, mostly good, amounting to 57 patients (54.3%), and empathy, mostly good, amounting to 58 patients (55.2%). There was a significant relationship between the quality dimensions and patient satisfaction as follows, p-value tangible is <0.001, p-value reliability is <0.001, p-value responsiveness is <0.001, p-value assurance is <0.001, p-value empathy is <0.001. The most dominant variable related to patient satisfaction is the reliability variable with OR = 147,589. In conclusion, there is a significant relationship between tangible, reliability, responsiveness, assurance, and empathy with patient satisfaction at Pertamina Bintang Amin Husada Hospital, Bandar Lampung.